Panhypopituitarism in adults: modern views and case analysis - L. M. Farkhutdinova (Архивъ внутренней медицины)
The article is devoted to the problem of panhypopituitarism, the diagnosis of which presents certain difficulties in connection with the combined lesion of several peripheral endocrine glands. Modern classification, etiopathogenesis, diagnosis and treatment of the disease are presented. Acquired hypopituitarism in adults develops, as a rule, at the age of 30-60 years, mostly women are affected. Pangypopituitarism is diagnosed when all pituitary tropic functions are affected, which is observed in case of damage to 90% of the adenohypophysis cells. The variety of clinical manifestations of the disease is determined by the different effects of pituitary hormones and the degree of their deficiency. The diagnosis is based on a history of etiological factors causing damage to the pituitary gland, and clinical signs of insufficiency of peripheral endocrine organs, which is confirmed by the results of laboratory studies. In hypopituitarism due to, for example, the growth of pituitary adenoma, the clinical picture develops gradually, and the disorder of the secretion of the pituitary tropic hormones usually occurs in the following sequence: the production of somatotropic hormone, gonadotropins, then thyrotropic hormone, adrenocorticotropic and, lastly, prolactin decreases. Neurosurgery or hemorrhage in the pituitary gland causes a rapid manifestation of the disease, and the severity of the condition is associated mainly with adrenal insufficiency. In the case of surgery for pituitary adenoma, there is a recommendation to determine morning blood cortisol on the 3rd day after surgery. Conservative treatment is aimed at compensating for hormone deficiency. According to the clinical significance of endocrine disorders, their correction is carried out in the following sequence — first, compensation for adrenal insufficiency, then thyroid, sex glands and somatotropin. In case of damage to the posterior lobe of the pituitary gland with the development of diabetes insipidus syndrome, replacement therapy for vasopressin deficiency is also required. The clinical example presented in the article reflects the difficulty of diagnosing and interpreting the data of hormonal studies in panhypopituitarism. An analysis of the described clinical situation shows the importance of understanding the pathogenesis of the disease when conducting a diagnostic search. Adequate replacement therapy can restore normal well-being in patients with hypopituitarism.